The Shattered Dreams: The Experience of Family Members Caring for a Relative Diagnosed with Schizophrenia: The Case of Amanuel Hospital, Ethiopia (Global Journal of Human-Social Science, 2016)
This study examined the experiences of family members caring for a relative diagnosed with schizophrenia in Ethiopia Previous studies indicated that family members providing care for their loved one with schizophrenia experienced many challenges in the course of care-giving Though family members experience both enrichments and challenges in caring for their loved one with mental illness little attention is paid to the comprehensive experiences of family members This study addressed the aforementioned issue and contributed to limited studies on psychiatric conditions in Ethiopia where there are limited services community service organizations or legal frame-works on mental illness The study used a qualitative case study approach In-depth interviews were conducted with eight purposely selected participants Content analysis was used to analyze the data and identify themes The study indicated a variety of impacts of caregiving such as psycho-social and economic as well as enrichments such as progress on the illness teaching their experiences deriving hope from the situation and satisfaction from sharing experiences with others Understanding caregivers experiences may be useful in prompting governments and service providers to invest in education and support programs aimed at helping caregivers to cope with this stress and deal with the problem behaviours associated with the illness
Keywords: schizophrenia –ethiopia –caregiving– coping